The Potential of Logistics Management for Supporting Tourists: A Case Study on Khao Soon in Chawang District Nakhon Si Thammarat Province - Wattanayotin, Tiranan; Kongyarit, Nuchakorn (International Journal of Supply Chain Management, 2020)
The objectives of this study were to examine the logistics management potential to support tourists in the Khao Soon area and to suggest ways of tourism potential development in the Khao Soon area, Chawang District, Nakhon Si Thammarat Province in accordance with tourists’ needs. The instruments used in this research were 330 sets of questionnaires accidentally given to tourists and an interview with five interviewees from government agencies, private organizations, and entrepreneurs by using purposive sampling. The data were expressed as percentage, means, standard deviations, t-test, and one-way analysis of variance (F-test). The findings showed that tourists placed importance on cooperation in the community and attraction in tourist destinations including the availability of services for personnel and places that are ready to support tourists. In view of tourists, things needed for improvement are the physical flow like readiness in route conditions to reach tourist attractions, the information flow including information service and maps showing tourist spots for tourists to access information, and the financial flow such as offering more multi-payment services to facilitate tourists by paying via QR Code or Prompt Pay. From the perspective of public/private agencies and entrepreneurs, the emphasis was on the physical flow with the development of routes to access tourist sites for more convenience in order to promote tourism and the information flow like promoting the public relations of tourist information to become more well-known via social media such as websites or Facebook. Entrepreneurs also wanted tourist spots to be publicized for recognition and required the development of service to meet the needs of tourists and sustainability in tourism. The findings showed that different demographic characteristics revealed significant and non-significant differences toward the potential of logistics management to support tourists at the 0.05 level.